ANALYSIS OF PUBLIC INTEREST PERCEPTIONS TOWARD GOLD INVESTMENT (A STUDY IN TANETE RIATTANG DISTRICT, BONE REGENCY) - NURHASANAH; ABDULAHANAA; IDA FARIDA (Institut Agama Islam Negeri (IAIN) Bone, 2026)
Abstract This study aims to analyze public perception of gold investment, identify factors that affect investment interest, and examine gold investment practices from an Islamic perspective in Tanete Riattang District, Bone Regency. The research uses a descriptive qualitative approach with a field study method. Data were collected through in-depth interviews and documentation of 15 selected informants using purposive sampling techniques, then analyzed with the Miles and Huberman model through data reduction, data presentation, and conclusion drawn. The results of the study show that the public views gold investment as a safe, stable, liquid, and able instrument to maintain the value of wealth. These perceptions are influenced by experience, social environment, family, and digital information. However, investment interest is still influenced by economic limitations and low financial literacy. From an Islamic perspective, gold investment is allowed as long as it meets sharia principles. This research provides an empirical contribution on the importance of Islamic financial literacy in shaping perceptions and encouraging interest in gold investment in the community. Abstrak Penelitian ini bertujuan menganalisis persepsi masyarakat terhadap investasi emas, mengidentifikasi faktor-faktor yang memengaruhi minat investasi, serta mengkaji praktik investasi emas dalam perspektif Islam di Kecamatan Tanete Riattang, Kabupaten Bone. Penelitian menggunakan pendekatan kualitatif deskriptif dengan metode studi lapangan. Data dikumpulkan melalui wawancara mendalam dan dokumentasi terhadap 15 informan yang dipilih menggunakan teknik purposive sampling, kemudian dianalisis dengan model Miles dan Huberman melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa masyarakat memandang investasi emas sebagai instrumen yang aman, stabil, likuid, dan mampu menjaga nilai kekayaan. Persepsi tersebut dipengaruhi oleh pengalaman, lingkungan sosial, keluarga, dan informasi digital. Namun, minat investasi masih dipengaruhi oleh keterbatasan ekonomi dan rendahnya literasi keuangan. Dalam perspektif Islam, investasi emas diperbolehkan selama memenuhi prinsip syariah. Penelitian ini memberikan kontribusi empiris mengenai pentingnya literasi keuangan syariah dalam membentuk persepsi dan mendorong minat investasi emas pada masyarakat.